2015
DOI: 10.1007/978-3-319-17121-0_41
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Field Fundus Autofluorescence for Retinitis Pigmentosa and Cone/Cone-Rod Dystrophy

Abstract: Retinitis pigmentosa and cone/cone-rod dystrophy are inherited retinal diseases characterized by the progressive loss of rod and/or cone photoreceptors. To evaluate the status of rod/cone photoreceptors and visual function, visual acuity and visual field tests, electroretinogram, and optical coherence tomography are typically used. In addition to these examinations, fundus autofluorescence (FAF) has recently garnered attention. FAF visualizes the intrinsic fluorescent material in the retina, which is mainly li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…2224 In patients with RP, the area of abnormal hypoautofluorescence correlated inversely with the visual field areas, suggesting that the extent of retinal degeneration in the periphery seen on UWF-FAF impacts peripheral vision. 23 Likewise, the abnormal autofluorescence centered in the macula in patients with cone and cone-rod dystrophy was also correlated with the I4e visual field area in those patients. 22 …”
Section: Discussionmentioning
confidence: 86%
“…2224 In patients with RP, the area of abnormal hypoautofluorescence correlated inversely with the visual field areas, suggesting that the extent of retinal degeneration in the periphery seen on UWF-FAF impacts peripheral vision. 23 Likewise, the abnormal autofluorescence centered in the macula in patients with cone and cone-rod dystrophy was also correlated with the I4e visual field area in those patients. 22 …”
Section: Discussionmentioning
confidence: 86%
“…Fundus autofluorescence (FAF) and optical coherence tomography (OCT) imaging have greatly improved the characterisation of IRDs. Using wide-field FAF, Oishi et al 36 demonstrated an association between abnormal AF and the severity of functional impairment in COD/CORD, also correlating the extent of reduced autofluorescence with symptom duration 37. These findings are substantiated by their correlation with ERG abnormalities 38.…”
Section: Genetic and Clinical Characteristics Of Cod And Cordmentioning
confidence: 96%
“…The FAF represents lipofuscin from predominantly the retinal pigment epithelium (Mercado & Louprasong, 2015). Therefore, FAF is useful for RP diagnosis (Oishi et al, 2016; Robson et al, 2003). In RP eyes, annular enhancement findings are observed in the macular region, whereas granular and mottled attenuation regions are observed in the peripheral region (Oishi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%